Studi Analisis: Pengaruh Disiplin Kerja Dan Motivasi Terhadap Kinerja Karyawan dengan Mediasi Kepuasan Kerja Di PT. T - Rizky, Muhammad; Maksum, Apid Hapid (Fakultas Teknik Universitas Tulang Bawang, 2024)
The aim of this research is to analyze the influence of work discipline and work motivation with the mediating variable namely job satisfaction on employee performance at PT. T, either directly or indirectly. This research uses a causal approach and involves all employees PT. T. The sample in this research is a saturated sample of 39 employees PT. T. Data collection is carried out through questionnaires. This research uses a approach quantitative and analyzes data using statistical analysis, using Outer Model, Inner Model and Hypothesis Testing. PLS (Partial Least Square) software was used to process the data. The research results showed that work discipline directly had a significant effect on employee performance with a probability value of 0.044 < 0.050, while work motivation and job satisfaction had no effect on employee performance with a probability value of 0.871 > 0.050 , 0.861 > 0.050, then job satisfaction which is a mediating variable on work discipline and work motivation indirectly has no influence on employee performance with a probability value of 0.950 > 0.050, 0.873 > 0.050 at PT. T. Keywords: Employee Performance, Hypothesis Test, Inner Model, Job Satisfaction, Outer Model, Work Discipline, Work Motivation